Book Review (Demography: Techniques and Analysis) by Asis Kumar Chattopadhyay and Anuj Kumar Saha (Economic Journal of Nepal, 2015)
Not available. The Economic Journal of Nepal  Vol. 35, No. 4, October-December 2012 (Issue N0. 140)Page: 290-291